Patient perspectives and treatment regret after de‐escalated chemoradiation for human papillomavirus‐positive oropharyngeal cancer: Findings from a phase II trial. Issue 8 (8th April 2019) - Shaverdian, Narek; Hegde, John V.; Felix, Carol; Hsu, Sophia; Basehart, Vincent; Steinberg, Michael L.; Chen, Allen M.
Abstract: Background: We evaluated priorities, expectations, and regret among patients treated on a phase II trial of de‐escalated chemoradiation for human papillomavirus (HPV)‐positive oropharyngeal cancer. Methods: Eligibility included stage III/IV squamous cell carcinoma of the oropharynx, p16‐positivity, age ≥18 years, and Zubrod score 0‐1. Participants were surveyed with validated measures evaluating their treatment experience. Results: Twenty‐four of 27 (89%) patients participated with a median follow‐up of 24 months. Twenty‐three subjects (96%) selected "being cured" or "living as long as possible" as top priority. No patient reported any regret about the decision to enroll on a de‐escalation protocol. Sixteen participants (67%) found retrospectively reported long‐term swallowing function to be either better than or as originally expected. Conclusions: These data offer a baseline landscape of perspectives and priorities for patients treated with de‐escalation for HPV‐positive oropharyngeal carcinoma and provide support to the fundamental premise underlying ongoing efforts to establish a new standard of care.